Weaponizing Social Media in Pakistan: Analyzing the Multifaceted Connections of Technological Determinism and Information Warfare - Mahnoor Anwar; Hina Shahid; Hafiz Muhammad Sheraz, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
Due to the recent technological evolution, states and civilizations have become trapped in a state of technological determinism or dependency thereby increasing their exposure or interaction to social media. This study brings together the context of information warfare being conducted through social media and how technological determinism further fuels its results. The study explores if information warfare conducted through social media has exposed elements such as cultural extinction and xeno-centrisim in the Pakistani society. A survey was conducted which involved around 200 respondents following the non-probability method and specifying the respondents to be working professional from the age of 25 and above. The results indicated that this issue did persist in Pakistan and the public was slowly being brain washed through information warfare conducted using social media by foreign elements like India and America and thus turning public perception of Pakistan according to will of the foreign elements and stopping them form the path of development.